Pengembangan Media Pembelajaran Augmented Reality Berbasis Lingkungan Sekitar Cekdam di Desa Tugu Sempurna untuk Siswa SMA - Euis Nur Af'idah; Yunita Wardianti; Fitria Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the design of developing augmented reality learning media based on the environment around the check dam in Tugu Perfect Village for high school students and to determine the feasibility of developing augmented reality learning media based on the environment around the check dam in Tugu Perfect Village for high school students in terms of validity and practicality. This research was carried out at Tugu Perfect State High School and in the environment around the check dam in Tugu Perfect Village. The research model used by ADDIE, however, has only reached the implementation stage. The test subjects for this research were validators, educators, and students. The data collection technique in this research uses media validity analysis, language, material, and media practicality analysis. The data collection instruments used by researchers were interview sheets, questionnaires, and observations. The research results showed that the average value of the one to one test was 88.73%, the small group test was 90.35%, and the field test was 74.06%. In conclusion, augmented reality learning media can increase student participants' learning motivation. Keywords: Augmented reality, Learning Motivation, Development